Impact of iron folic acid tablet utilization on the prevalence of anemia amongst mothers under Rch programme - Singh, A B; Kandpal, S D; Gupta, S K; Chandra, R; Srivastava, V K; Negi, K S (Indian Journal of Community Health, 2006)
Research question: What is the effect of IFA Tablet utilization on prevalence of anemia. Objectives: 1- To study the utilization of IFA tablets among pregnant and lactating women in Dehradun district. 2- To study the association of anemia with IFA tablet utilization. Study design: Cross-Sectional study. Setting: Twenty villages of Doiwala Block, Dehradun Participants: Pregnant and lactating women. Study period: Junary 2004 to Feb 2005. Statistical Analysis : Percentage, Chi-square test. Results: Prevalence of anemia among those women who had not received Iron Folic Acid tablets was found to be 77.9% as compared to 57.7% among those women who had received the IFA tablets.